Probation control as a compulsory measure of educational influence in the criminal legislation of the Republic of Kazakhstan - Tatikov, R.U.; Nagornov, K.I. (Karagandy University of the name of academician E.A. Buketov, 2025)
In the new criminal law in the Republic of Kazakhstan adopted in 2014, the list of compulsory educational measures applied to juvenile offenders has been somewhat updated and supplemented with a new measure in the form of establishing probation control. The authors of the work attempted to give a comprehensive legal description of this compulsory measure, while paying attention to some imperfections of the provisions of the Criminal Code of the Republic of Kazakhstan, the Criminal Execution Code of the Republic of Kazakhstan and the Law of the Republic of Kazakhstan “On Probation,” which negatively affect its preventive potential and application practice. In particular, the article draws attention to the not quite advantageous placement of the measure in the list of compulsory educational measures, to the imperfection of the wording of the content of the measure presented in Part 9 of Article 85 and Part 2 of Article 44 of the Criminal Code of the Republic of Kazakhstan, for the presence of substantial similarity and even identity of probation control as a compulsory measure of educational influence and some other measures provided for by the Criminal Code of the Republic of Kazakhstan, for the absence of a minimum period and criminological validity of the maximum period of application of the measure, for the lack of differentiation of the terms of application of the measure depending on the type of criminal offense and the category of severity of the crime. During the consideration of the problems, the authors expressed separate considerations. They proposed specific measures to eliminate them by improving the legal basis of probation control as a compulsory measure of educational influence.
Пробациялық бақылау Қазақстан Республикасының қылмыстық заңнамасында тәрбиелік ықпал ету мақсатындағы мәжбүрлеу шарасы ретінде
Пробационный контроль как принудительная мера воспитательного воздействия в уголовном законодательстве Республики Казахстан
Keywords: minors; compulsory measures of educational influence; probation control; content; responsibilities; terms of use